Advances in agronomy. - Sparks, Donald L., 1953- (Elsevier Academic ; Elsevier Science [distributor], 2005)
Volume 87 contains five excellent reviews dealing with environmental sustainability/quality and plant improvement that will be of great interest to plant and soil scientists as well as professional in related fields. Topics discussed in this volume include: Factors affecting antibiotic persistence in the terrestrial environment, antibiotic resistant bacteria and human health concerns, soil amendments and amelioration, human aspects of irrigation management, nitrogen use efficiency in cereal-based agricultural systems on a worldwide basis, and much more. * Includes over 35 figures and 50 tables with the most advanced data * Offers 5 full detailed chapters dedicated to the most up-to-date issues and discoveries in agronomy science * Maintains the highest impact factor among serial publications in Agriculture * Presents an analysis of the efficiency of fertilizer nitrogen in cereal production * Includes over 35 figures and 50 tables with the most advanced data * Offers 5 full detailed chapters dedicated to the most up-to-date issues and discoveries in agronomy science * Maintains the highest impact factor among serial publications in Agriculture * Presents an analysis of the efficiency of fertilizer nitrogen in cereal production.